Feasibility study of nuclear excitation by electron capture using an electron beam ion trap - Wang, Yumiao; Ma, Zhiguo; Yang, Yi; Fu, Changbo; He, Wanbing; Ma, Yugang (Frontiers in Physics, 2023)
The nuclear excitation by electron capture (NEEC) mechanism is considered to be one of the most effective ways to excite nuclear isomers. Despite being proposed over 50 years ago, direct experimental evidence of NEEC is yet elusive. In this study, we propose an experimental scheme to examine the NEEC process using an electron beam ion trap (EBIT). In an EBIT, highly charged ions are bombarded by an electron beam, which can result in excitation of the nuclei in the trap through mechanisms such as NEEC and Coulomb excitation (CE), etc. Our calculations show that the total rates of NEEC production for some nuclei can reach over 0.1 /s, which is higher than these from other mechanisms like CE. The proposed scheme may result in the confirmation of the existence of NEEC, and can also be used to study atomic nuclear excitation related processes.